Graffiti, street art and copyright - Bonadio, Enrico (2018)
This short note examines whether street and gra ti art can and should be protected by copyright. Indeed, cases where corpo- rations have used these forms of art to promote their products are increasingly common, which shows that these artworks are particularly vulnerable to misappropriation. In addition to expanding on whether tags and throw-ups can be considered original enough to attract copyright, I will focus on whether unsanctioned street and gra ti art deserve such legal protection and in general on artists and writers’ attitude towards copyright. The note also draws from semi-structured interviews I’ve recently conducted with several street artists and writers.